AJL’s Sydney Taylor Awards for Children’s Literature - Barancik, Sue (Judaica Librarianship, 1993)
This past year, I have had the privilege of serving once again as Chairman of the Sydney Taylor Book Award Committee, having chaired this committee in 1983 and 1984. In the space of these few short years, I have marveled at the growth in quality of Judaica for children. Although there were certainly excellent books during my earlier stint as chairman, the 46 books that my committee and I reviewed this year showed a delightfully marked increase in quality of illustrations, uniqueness of topic, and sophistication in format.